Inhibiting Factors in Automotive Courses at the Job Training Centre - Sutiman, Sutiman; Jaedun, Amat; Siddiq, Mochammad Baharudin; Suyitno, Suyitno; Nurtanto, Muhammad (Universitas Pendidikan Ganesha, 2022)
Indonesia faces unemployment and employment problems. In February 2021, the number of unemployed people aged 15 years and over in Indonesia reached 8.7 million. On the other hand, the Covid-19 pandemic has disrupted economic activity, uncertainty, and 6.4 million workers were forced to be laid off. The unemployment rate is one of the problems that Indonesia’s problems, especially during the Covid-19 pandemic. The government, through the Minister of Manpower, seeks to control the unemployment rate during the Covid-19 pandemic by conducting various competency and productivity-based training through Education and training programs organized by the Vocational Training Centre (BLK) and the development program for expanding job opportunities for workers or laborers affected by the pandemic. This study aims to describe the inhibiting factors during the implementation of automotive courses and how the impact of these inhibiting factors on the management of automotive courses in BLK in the future. Respondents consisted of 17 teachers and managers in the automotive sector BLK. Data was collected using a questionnaire in the form of a questionnaire tested using Product-moment Person, expert judgment, and Cronbach’s Alpha coefficient. The findings show that the inhibiting factors include the curriculum with 65.11%, teachers 54.67%, course participants 57.22%, managers 65.52%, facilities 78.31%, funds or budget of 54.12%, the government by 51.18%, and the community by 60.71%. The research was limited to teachers and BLK managers in the automotive sector in Yogyakarta. Furthermore, future research is expected to involve various parties involved and supporting factors outside the aspects that have been studied.